Bibliometric Analysis of Foodborne Pathogen Research in the Year Range 2013-2023 Based on Scopus Web Data - Sophian, Alfi; Purwaningsih, Ratna (Universitas Tanjungpura, 2023)
Bibliometric analysis is a methodology that can be used to investigate patterns in publications based on data cited from academic literature. This research is conducted to comprehensively analyze selected topics. This paper presents the evolution and structure of the chosen research topic. The goal is to obtain an overview of information about the foodborne pathogen research that has been conducted, with the hope that this information can provide insights and guidance for further research related to foodborne pathogens. This paper is also expected to open up new opportunities for identifying gaps in the analysis of potential innovations in foodborne pathogen research, which can serve as a reference for future studies. Bibliometric literature analysis is centred around the main components using Bibliometrics and VOSviewer. This analysis is based on articles published in Scopus journals from 2013 to 2023. Data extracted from the Scopus web shows an increasing trend year by year, with the United States having the highest number of articles, totalling 3,109, and 22 countries with the lowest number of articles. As for the categories based on the source of information, they can be grouped into journals, books, book series, conference proceedings, and undefined sources. The visualization network shows five different colours, with each colour representing the number of clades generated from the analysis. Based on this, it can be concluded that a significant amount of research related to foodborne pathogens has been conducted, with many studies focusing on pathogens in animals, food microbiology, food control, antibiotic resistance, and pathogens in non-human subjects.